Design of a didactic guide based on the TPACK Model in the teaching of statistics - Bonifaz Vallejo , Oswaldo Patricio; Castillo Martínez, Cristhian Patricio (SATHIRI, 2025)
In the world there are several pedagogical approaches and currents that adapt or change to current contexts in response to sociocultural evolution, technological advances and regional needs, typical of the educational community. The present exploratory research was carried out under a mixed approach, and aims to design a teaching guide based on the TPACK Model (Technological, Pedagogical and Content Knowledge), which identifies the necessary knowledge that teachers must have, in order to improve the teaching-learning process, through the appropriate integration of technologies for teaching the subject of Statistics. The research was done in a higher education institution in the Ecuadorian Amazon. Within the statistical process of validation of results of the 151 students surveyed, was carried out the calculation of Cronbach's Alpha, obtaining a coefficient of 0.89 of the 36 variables under study, and the calculation of the correlation matrix was also carried out, which made it possible to determine that there is no presence of redundant variables, and demonstrate the need for strengthen the digital skills of Statistics teachers, specifically in the management of specialized software and the effective integration of technologies in classes. The application of a teaching guide based on the TPACK model, designed in response to the identified requirements, represents a viable solution to improve the teaching-learning process of Statistics in the institution under study. By combining technological, pedagogical and content knowledge, this guide seeks to enhance the use of digital tools and effective pedagogical techniques in the teaching of this subject.
Keywords: TPACK model; Technologies; Education; Statistics